A note on some spaces Lγ of distributions with Laplace transform - Salvador Pérez Esteva (International Journal of Mathematics and Mathematical Sciences)
In this paper we calculate the dual of the spaces of distributions Lγ introduced in [1]. Then we prove that Lγ is the dual of a subspace of C∞(ℝ).